Cost variation analysis of various brands of anti-retroviral agents currently available in Indian market: an economic perspective study - R., Anusha; A., Geetha (International Journal of Basic & Clinical Pharmacology, 2022)
Background: The aim was to analyze the percentage cost variations among different brands of the commonly prescribed anti-retroviral agents in the treatment of human immunodeficiency virus. Methods: The cost of different brands of commonly used Anti-Retroviral agents was sorted out by referring latest Indian drug index online, drug today, current index of medical specialties, Indian drug review. Results: The percentage variation in the cost was above 100% with most of the commonly used anti-retroviral agents. Overall sequinafir 500 mg shows maximum cost variation of 1490.3%, while nelfinavir (625 mg) shows minimum cost variation of 6.1% in single drug therapy. Lamivudine 300 mg and tenofovir 300 mg combination shows maximum cost variation of 14055% whereas, lamivudine 150 mg, zidovudine 300 mg and efavirenz 600 mg shows minimum cost variation of 10% in combination drug therapy. Conclusions: HIV is the most common infectious, life-threatening disease and drugs are to be prescribed for life-long period. If a costly brand is prescribed, the patients cannot afford to pay more money for their treatment. This also leads to poor patient compliance, dissatisfaction and failure of the treatment. Ideally, therefore, the drugs should be prescribed in such a way, to save the patient's economic burden and enhance the compliance of the treatment.